Anti-SARS-CoV-2 glyco-humanized polyclonal antibody XAV-19: phase II/III randomized placebo-controlled trial shows acceleration to recovery for mild to moderate patients with COVID-19 - Poulakou, Garyfallia; Royer, Pierre-Joseph; Evgeniev, Nikolay; Evanno, Gwénaëlle; Shneiker, Françoise; Marcelin, Anne-Geneviève; Vanhove, Bernard; Duvaux, Odile; Marot, Stéphane; Calvez, Vincent (Frontiers in Immunology, 2024)
III randomized placebo-controlled clinical trial including 279 patients hospitalized or not, with mild to moderate COVID19 (7-point ordinal WHO score at 2, 3 or 4 at randomization), treatment with XAV-19 did accelerate significantly recovery defined by a reduction of 1-point or more of the 7-point ordinal scale. Strengths of XAV-19 are its affordability and its activity against SARS-CoV-2 variants. Next trials should confirm the therapeutic interest of XAV-19 for high-risk patients with mild to moderate COVID-19.